Kingdom ethics : following Jesus in contemporary context - Stassen, Glen Harold, 1936-2014 (InterVarsity Press, 2003)
Examines Christian ethics based on the study of Jesus' life and teachings, especially the Sermon on the Mount. Covers current issues such as just war, life at its beginning and ending, biotechnology, and sexuality.